Stunting Determinant on Toddler Age of 12–24 Months in Singaparna Public Health Center Tasikmalaya Regency - Erwina Sumartini; Dida Akhmad Gurnida; Eddy Fadlyana; Hadi Susiarno; Kusnandi Rusmil; Jusuf Sulaeman Effendi (Global Medical & Health Communication (GMHC), 2019)
Stunting is a physical growth failure condition signed by height based on age under −2SD. The research goal is knowing the dominant factor associated with stunting on toddler age of 12–24 months in the working area of Singaparna Public Health Center Tasikmalaya regency. The research applies to the cross-sectional design of gender, weight, exclusive breastfeeding history, completeness immunization, and clinically healthy variables, while case-control is for nutrition intake variable. The sample was a total sampling of 376 toddlers, then 30 for case and control group with the simple random method from December 2017 to February 2018. The instrument is a questionnaire, food frequency questionnaire (FFQ), and infantometer. Data analyzed in several ways; univariable, bivariable with chi-square, and multivariable with logistic regression. Research result shows stunting prevalence was 22.5%, next pertain factor of stunting are gender (POR=0.564, 95% CI=0.339–0.937, p value=0.011), exclusive breastfeeding giving history (POR=1.46, 95% CI=1.00–2.14, p value=0.046), and clinically health (POR=1.47, 95% CI=1.00–2.16, p value=0.044). Moreover, dominant factor were gender (OR=0.56, 95% CI=0.339–0.937, p value=0.027) and clinically health (OR=1.68, 95% CI=1.022–2.771, p value=0.041). Thus, gender and clinical health are stunting determinant factors. Children’s health should increase to create maximum growth. DETERMINAN STUNTING PADA ANAK USIA 12–24 BULAN DI PUSKESMAS SINGAPARNA KABUPATEN TASIKMALAYAStunting merupakan kondisi kegagalan pertumbuhan fisik yang ditandai dengan tinggi badan menurut usia berada di bawah −2SD. Penelitian ini bertujuan mengetahui faktor determinan stunting pada anak usia 12–24 bulan di wilayah kerja Puskesmas Singaparna Kabupaten Tasikmalaya. Penelitian menggunakan desain cross-sectional untuk variabel jenis kelamin, berat badan lahir, riwayat ASI eksklusif, kelengkapan imunisasi, dan  sehat secara klinis, sedangkan desain case-control untuk variabel asupan nutrisi. Pengambilan sampel secara total sampling sejumlah 376 anak, selanjutnya diambil 30 anak untuk kelompok kasus dan kontrol dengan metode random sederhana periode Desember 2017 hingga Februari 2018. Instrumen menggunakan kuesioner, food frequency questionaire (FFQ), dan infantometer. Analisis data dilakukan secara univariabel, bivariabel dengan chi-square, dan multivariabel dengan regresi logistik. Hasil penelitian menunjukkan prevalensi stunting sebesar 22,6%, faktor yang berhubungan dengan stunting di antaranya jenis kelamin (POR=0,564; IK95%=0,339–0,937; p=0,011), riwayat pemberian ASI eksklusif (POR=1,46; IK95%=1,00–2,14, p=0,046), dan sehat secara klinis (POR=1,47; IK95%=1,00–2,16; p=0,044). Faktor dominan yang berhubungan dengan stunting adalah jenis kelamin (OR=0,56; IK95%=0,339–0,937; p=0,027) dan sehat secara klinis (OR=1,68; IK95%=1,022–2,771; p=0,041). Jenis kelamin dan sehat secara klinis merupakan faktor determinan stunting. Kesehatan anak perlu ditingkatkan untuk menciptakan pertumbuhan anak yang maksimal.